PENGEMBANGAN CD INTERAKTIF PEMBELAJARAN MATEMATIKA PADA MATERI STATISTIKA - Utaminingsih, Rr. Tri; Nayazik, Akhmad; Wahyuni, Arie (Universitas Muhammadiyah Purworejo, 2020)
The purpose of this study is to get results of interactive CD development valid, practical and effective statistical material. The type of this research is development research which refers to ADDIE (Analysis, Desigh, Development, Implementation aand Evaluatin). The subject of this research is xi grade of SMK Bhakti Praja 2 Batang. The instrument used in this research is (1) media expert evaluation questionnaire (2) material expert evaluation questionmire (3) student response questionnaire (4) student evaluation questions. The method used in gathering the data is, by doing observations, questionnaires, tests, and documentation. The results of this study show the validty quality of the interactive CD meetr valid criteria shown by media experts who obtained and average score of 3,8 from maximum score 4 which is good, while material experts get 4,1 from maximum score 5 which means good. Quality of practicality of learning devices practical criteria indicate by the average score of student 4,01 from maximum score 5 which means good. Quality of effectiveness of learning devices in terms of students’ mathematical communication skills meet practical criteria shown by the percentage of students completeness 87,5% which means good. Of the 32 student, there are 28 students who had completed grads.Kata kunci: Development, Interactive CD, ADDIE model.